2018
DOI: 10.1051/0004-6361/201833481
|View full text |Cite
|
Sign up to set email alerts
|

Breaking degeneracies in modified gravity with higher (than 2nd) order weak-lensing statistics

Abstract: General relativity (GR) has been well tested up to solar system scales, but it is much less certain that standard gravity remains an accurate description on the largest, that is, cosmological, scales. Many extensions to GR have been studied that are not yet ruled out by the data, including by that of the recent direct gravitational wave detections. Degeneracies among the standard model (ΛCDM) and modified gravity (MG) models, as well as among different MG parameters, must be addressed in order to best exploit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 107 publications
(124 reference statements)
2
58
0
1
Order By: Relevance
“…We use a subset of the DUSTGRAIN-pathfinder (Dark Universe Simulations to Test GRAvity In the presence of Neutrinos) cosmological N-body simulations, which is part of a numerical project aimed at investigating possible cosmic degeneracies, such as the ones between f (R) models and massive neutrinos, that is the subject of the present work. In a series of recent papers, these simulations have been exploited to investigate several features related to weak-lensing statistics Peel et al 2018b), to the abundance of massive haloes (Hagstotz et al 2018) and to explore cosmic degeneracies using machine learning techniques (Peel et al 2018a;Merten et al 2018). The DUSTGRAIN-pathfinder runs have been performed using the MG-Gadget code (Puchwein et al 2013), which is a modified version of GADGET (Springel 2005) implementing the Hu & Sawicki (2007) f (R) gravity model, with a mixture of cold and hot DM components, the latter made up of massive neutrinos.…”
Section: N-body Simulations and Halo Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a subset of the DUSTGRAIN-pathfinder (Dark Universe Simulations to Test GRAvity In the presence of Neutrinos) cosmological N-body simulations, which is part of a numerical project aimed at investigating possible cosmic degeneracies, such as the ones between f (R) models and massive neutrinos, that is the subject of the present work. In a series of recent papers, these simulations have been exploited to investigate several features related to weak-lensing statistics Peel et al 2018b), to the abundance of massive haloes (Hagstotz et al 2018) and to explore cosmic degeneracies using machine learning techniques (Peel et al 2018a;Merten et al 2018). The DUSTGRAIN-pathfinder runs have been performed using the MG-Gadget code (Puchwein et al 2013), which is a modified version of GADGET (Springel 2005) implementing the Hu & Sawicki (2007) f (R) gravity model, with a mixture of cold and hot DM components, the latter made up of massive neutrinos.…”
Section: N-body Simulations and Halo Samplesmentioning
confidence: 99%
“…Lesgourgues & Pastor 2006;Marulli et al 2011;Costanzi et al 2014;Battye & Moss 2014;Villaescusa-Navarro et al 2014;Enqvist et al 2015;Roncarelli et al 2015;Zennaro et al 2018;Poulin et al 2018a). However, it has been recently shown that a strong observational degeneracy exists between some modified gravity (MG) models and the total neutrino mass (Motohashi et al 2013;He 2013;Baldi et al 2014;Giocoli et al 2018), giving rise to an intrinsic limitation of the discriminating power of many standard cosmological statistics (Peel et al 2018b;Hagstotz et al 2018). MG models represent one of the most viable alternatives to explain cosmic acceleration (for a review see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The DES Collaboration considers neutrino mass and extensions to GR in the same analysis [36], although they only state the resulting constraints on the MG parameters and not the neutrino masses. There are some promising signs that certain observables may be better at reducing or even breaking this degeneracy, such as higher-order weak lensing statistics [37] and weak lensing tomographic information at multiple redshifts [38]; as well as techniques that are superior at distinguishing models such as machine learning [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…A consideration of a broad range of cosmological models has been explored for S/N peak distributions (e.g. Yang et al 2011;Liu & Haiman 2016;Liu et al 2016;Martinet et al 2018;Peel et al 2018) but these simulations and other works do not include both the impact of summed neutrino mass and baryonic physics. In this paper we focus on baryonic physics and massive neutrinos and restrict our consideration to the two sets of cosmologies of BAHAMAS based on the WMAP 9-yr mission (WMAP 9, Hinshaw et al 2013) and the Planck 2015 mission (Planck 2015, Planck Collaboration et al 2016c parameters.…”
mentioning
confidence: 99%